2017
DOI: 10.1590/abd1806-4841.20175070
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the incidence of rash, Stevens-Johnson syndrome and toxic epidermal necrolysis in patients taking lamotrigine: a systematic review of 122 randomized controlled trials

Abstract: Lamotrigine is an antiepileptic drug used for the treatment of epilepsy, bipolar disorder and numerous off-label uses. The development of rash significantly affects its use. The most concerning of these adverse reactions is Stevens-Johnson syndrome/toxic epidermal necrolysis. We performed a systematic review of randomized controlled trials using lamotrigine as a monotherapy to quantify the incidence of cutaneous reactions, particularly Stevens-Johnson syndrome/toxic epidermal necrolysis. Of a total of 4,364 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…The most concerning of this adverse reactions is SJS/toxic epidermal necrolysis (TEN). The incidence of SJS/TEN is 0.04%, which is the highest frequency in anti-epileptic drugs [16]. But LTG is less teratogenic so that there is a tendency to be prescribed for young women.…”
Section: Discussionmentioning
confidence: 99%
“…The most concerning of this adverse reactions is SJS/toxic epidermal necrolysis (TEN). The incidence of SJS/TEN is 0.04%, which is the highest frequency in anti-epileptic drugs [16]. But LTG is less teratogenic so that there is a tendency to be prescribed for young women.…”
Section: Discussionmentioning
confidence: 99%
“…A rash is a common side effect of LTG treatment, occurring in 8.3%, with half of these withdrawing medications as a consequence [34]. This may be an over cautious measure, as separate studies have found that only 0.04% of new users develop SJS/TEN, and less than 0.1% develop DRESS [35]. Many clinicians are aware of appearance or aggravation of acne in those staring lamotrigine, however literature on this is sparse [36].…”
Section: Lamotriginementioning
confidence: 99%
“…Furthermore, among 122 randomized controlled trial of LTG monotherapy totalizing 18,698 patients, Bloom and Amber found only 8.3% of benign and self‐limited morbiliform rash but 0.04% of Stevens‐Johnson syndrome and Lyell syndrome . Fatal severe cutaneous adverse reactions related to LTG use are extremely rare and estimated at 0.01 per 1000 patient‐year (3.5% of severe cutaneous adverse reactions) and imposes strict compliance with the drug scheduled regimen as well as the immediate cessation of drug intake at first signs suggestive of immunoallergic reactions (eg, high fever, influenza‐like symptoms, conjunctival itching, cutaneous erythema, progressive blistering, mucosal erosions, or hematological abnormalities) .…”
Section: The Safety and Tolerance Of Lamotrigine Appears Among The Himentioning
confidence: 99%